We Belong to the Trees, A Collection of Short Stories - Mopai, Keletso (School of Languages and Literatures, 2025)
Set in the mid 90s on the backdrop of South Africa's new found democracy, the ten stories explore the murder of a security guard at a farm in the Afrikaner town of Tzaneen, Limpopo. The aftermath exposes power dynamics between white bosses and Black workers in the area. Told from different perspectives and voices – young, adult, Black and white characters – each story provides accounts surrounding the murder. They reflect conflicts that arise, and as such relationships are tested; some break, others repair, while some are lost forever. In the past years since 1994, there have been several deaths of farm workers in Tzaneen. The stories are also an attempt to discuss the implications of the violence against the working class in the farming industry. At its core, We Belong to the Trees highlights the tropical regions of Limpopo as the ordinary navigate Post-Apartheid South Africa. It implores one to think about issues such as land-restitution, violence, racism, poverty, crime, and greed. The main concern as a writer is to reflect my surroundings, discuss and dissect through storytelling. The work encompasses my fears and concerns as a South African.